Elaboração e implementação de modelo de gerenciamento de riscos com foco na avaliação da maturidade de empreendimentos de incorporação imobiliária - Maurício Ataide Machado (2018)
The companies active in the Brazilian real estate market have increased the concern with the reduction of the risks of the enterprises. One strategy is the introduction of methods for assessing the level of definition or maturity of the design process. The aim of this paper is the elaboration and implementation of a risk management framework, focusing on the level of definition of the design process, for the real estate projects, in the region of Belo Horizonte / MG. Using the Design Science Research (DSR) method, for the understanding of design process in real estate, the paper figure out the activities who could make changes on the process. Some evaluation itens were developed, sorted in categories, embracing the NBR 15.575:2013 requisites. An adaptation from the Project Definition Rating Index (PDRI) to be applied in the evaluation of definition level of the design process was created. Some experts in the theme were consulted for validate the tools. The level of definition from the building analyzed present that the it was appropriate for the design processo of real estate. The results point out that the tool seems to be an interesting resource to control, critical analysis and validation of the design process. The research project contribution is significant, since presents a new tool to design risk evaluation including performance-based concepts, applied regarding NBR 15.575:2013.